Glycophthalocyanines as photosensitizers for triggering mitotic catastrophe and apoptosis in cancer cells - Soares, Ana R. M.; Neves, Maria G. P. M. S.; Tome, Augusto C.; Carmen Iglesias-De La Cruz, M.; Zamarron, Alicia; Carrasco, Elisa; Gonzalez, Salvador; Cavaleiro, Jose A. S.; Torres, Tomas; Guldi, Dirk Michael; Juarranz, Angeles (Chemical Research in Toxicology, 2012)
Photodynamic therapy (PDT) is a treatment modality for different forms of cancer based on the combination of light, molecular oxygen, and a photosensitizer (PS) compound. When activated by light, the PS generates reactive oxygen species leading to tumor destruction. Phthalocyanines are compounds that have already shown to be efficient PSs for PDT. Several examples of carbohydrate substituted phthalocyanines have been reported, assuming that the presence of carbohydrate moieties could improve their tumor selectivity. This work describes the photoeffects of symmetric and asymmetric phthalocyanines with D-galactose (socalled GPh1, GPh2, and GPh3) on HeLa carcinoma cells and their involvement in cell death. Photophysical properties and in vitro photodynamic activities for the compounds considered revealed that the asymmetric glycophthalocyanine GPh3 is very efficient and selective, producing higher photocytotoxicity on cancer cells than in nonmalignat HaCaT. The cell toxiticy after PDT treatment was dependent upon light exposure level and GPh3 concentration. GPh3 causes cell cycle arrest at the metaphase stage leading to multiple spindle poles, mitotic catastrophe, followed by apoptosis in cancer cells. These effects were partially negated by the pancaspase inhibitor Z-VAD-FMK. Together, these results indicate that GPh3 is an excellent candidate drug for PDT, able to induce selective tumor cell death. (Chemical Equation Presented). © 2012 American Chemical Society.